Característica do solo, crescimento e composição química do capim-tifton sob adubação e irrigação com água residuária da piscicultura - Furtado, Francisca Mirlanda Vasconcelos (2015)
This work was carried out to evaluate the effects of nitrogen fertilization in areas of irrigated pastures with biofertilizados effluents from fish farming. Four doses of nitrogen fertilizer were used for 3 cycles of Tifton-85 grass cut every 28 days and irrigated with wastewater from fish farming. After each cutting the grass was fertilized with the respective doses of fertilizer. The design was completely randomized in a factorial 2 x 4 with four replicates. Four doses of nitrogen fertilizer dose corresponded to 0 to N; 198 kg N ha-1 yr-1 33% of the dose of N; 396 kg N ha-1 yr-1 66% of the dose of N; and 600 kg N ha-1 yr-1 corresponding to 100% of the dose of growth assessment the design was completely randomized using the nitrogen dosages described and four replications. The area per plot was used to harvest the fresh biomass to be analyzed, which was immediately measured on a digital scale pendulum for its determination. After all installments have their biomass values known and properly stored, they were sent to the laboratory of plant analysis Embrapa Mid-North. The collected biomass is fractionated into categories: whole plant (pseudo stem and leaf without senescent material), only pseudoculm, only leaf and senescent material. The stored material was taken for laboratory analysis of animal- nutrition LANA, Federal University Of Ceará. Analyzes to determine the levels of dry matter were held (MS), mineral matter (MM), ether extract (EE), crude protein (% N x 6.25 = PB). The cellular content of the contents (CC) and hemicellulose (HEM) were obtained following the post- analysis equations. The fiber values of neutral detergent fiber (NDF) and acid detergent fiber (ADF) were measured after preparation of the material to be analyzed in bags of TNT (100 g / m2) with dimensions of 4 x 5cm and engagement in analysis instrument fibers (Ankom220®). Nitrogen fertilization influenced the soil chemical characteristics as the base saturation and potential soil acidity in Tifton 85 irrigated pasture with fish farm effluents, where nitrogen (N) influenced positively to the growth of Tifton 85 irrigated with wastewater fish farming. Nitrogen fertilization in conjunction with wastewater from fish farming. The absence of nitrogen fertilization promoted increase in dry matter content in Tifton-85 grass, as well as high levels of ADF and NDF. Leaf fraction of Tifton 85 has a higher amount of organic compounds in relation to pseudoculm fraction, and this can change the true values of ether extract and crude protein. The wastewater fish farming along with the application of ammonium sulfate positive effect on the chemical composition of Tifton 85 grass.